Réponses

2014-09-09T21:58:24+02:00
A= - (- 14) + (- 12) + (+ 17) - (- 5) - (+ 33)
A = 14 - 12 + 17 + 5 - 33
A = 14 + 17 + 5 - 12 - 33
A = 36 - 45
A = - 9

B = 9 - 13 + 5 - (- 14 + 6 - 3)
B = 9 - 13 + 5 - (- 11)
B = 9 - 13 + 5 + 11
B = 9 + 5 + 11 - 13
B = 25 - 13
B = 12

C = - 10,8 - (0,8 + 1.2) - (- 12,6 + 4,9)
C = - 10,8 - (2) - (- 7,7)
C = - 10,8 - 2 + 7,7
C = - 11 + 7,7
C = - 3,3

D = 5 x (- 4) + 15 - 6 / (3)
D = - 20 + 15 - 2
D = - 22 + 15
D = - 7

E =  24 / (- 8) x (- 5) + 9
E = 3 x - 5 + 9
E = - 15 + 9
E = - 6
2014-09-09T22:01:25+02:00
A= - (- 14) + (- 12) + (+ 17) - (- 5) - (+ 33)
A = 14 - 12 + 17 + 5 - 33
A = 14 + 17 + 5 - 12 - 33
A = 36 - 45
A = - 9

B = 9 - 13 + 5 - (- 14 + 6 - 3)
B = 9 - 13 + 5 - (- 11)
B = 9 - 13 + 5 + 11
B = 9 + 5 + 11 - 13
B = 25 - 13
B = 12

C = - 10,8 - (0,8 + 1.2) - (- 12,6 + 4,9)
C = - 10,8 - (2) - (- 7,7)
C = - 10,8 - 2 + 7,7
C = - 11 + 7,7
C = - 3,3

D = 5 x (- 4) + 15 - 6 / (3)
D = - 20 + 15 - 2
D = - 22 + 15
D = - 7

E =  24 / (- 8) x (- 5) + 9
E = 3 x - 5 + 9
E = - 15 + 9 
E = - 6